The effectiveness of application of drawing activity occupational therapy against auditory hallucination symptoms - Sujiah Sujiah; Hernida Warni; Adi Fikrinas (Universitas Muhammadiyah Semarang, 2023)
Auditory hallucinations are the most common hallucinations in schizophrenia, experienced by more than 60% of people with schizophrenia. Patients who have hallucinations often become irrational and lose control of their actions, which can lead to homicide, suicide, and environmental destruction. This study aims to examine the effects of occupational therapy drawing exercises on auditory hallucination symptoms. This study used a quasi-experimental control group technique with a sample size of 40 respondents. The results showed an impact of occupational therapy on drawing activity on auditory hallucinations symptoms, with a p-value of 0.000, and a significant difference in the reduction of auditory hallucinations symptoms between the intervention and control group after occupational therapy with a drawing activity. Patients with auditory hallucinations are advised to engage in occupational therapy drawing activities to alleviate their symptoms.